Symposium: The Oxford School of Industrial Relations: Fifty Years after the 1965–1968 Donovan Commission: Introduction: Who Were the Oxford School and Why Did They Matter?. Issue 37 (September 2016) - Ackers, Peter
Abstract : The 'Oxford School of Industrial Relations', centred at Nuffield College, was one major instance of academics entering the 'corridors of power' and attempting to resolve national problems of unofficial strikes, inflation, and restrictive practices, most notably via the Royal Commission on Trade Unions and Employers' Associations (Donovan), 1965–68. For historians today, there are two reasons why this mattered. First, because, in effect, they had created a new social-science field of industrial relations. Oxford was not the only industrial relations centre, but during the 1950s and 1960s it was the strongest and most politically influential. Second, and more important at the time, the Oxford School addressed a central policy moment in the development of social-democratic 'bargained corporatism' and the role that trade unions might play in this. In many respects, the Oxford School were representative figures of the post-war progressive generation, dedicated to 'reconstruction'. It had had a powerful impact on public policy because its pluralist underpinnings were consistent with the needs of social-democratic public policy, sympathetic to trade unions, and could be translated into practical, applied public-policy solutions.